2022
DOI: 10.1097/rti.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Measurement Sites of Coronary-Computed Tomography Angiography-derived Fractional Flow Reserve

Abstract: Objectives: To investigate the optimal measurement site of coronary-computed tomography angiography-derived fractional flow reserve (FFRCT) for the assessment of coronary artery disease (CAD) in the whole clinical routine practice. Materials and Methods: This retrospective multicenter study included 396 CAD patients who underwent coronary-computed tomography angiography, FFRCT, and invasive FFR. FFRCT was measured at 1 cm (FFRCT-1 cm), 2 cm (FFRCT-2 cm), 3 cm (FFRCT-3 cm), and 4 cm (FFRCT-4 cm) distal to cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…These findings suggest that FFR CT measured at 2 cm distal to the target lesion had the highest performance in identifying lesion-specific ischemia. Overall, our results are consistent with the findings of previous study [ 15 , 16 , 18 , 24 ]. In our study, FFR CT was measured at four different sites along the same artery and our results showed that FFR CT measured at 2 cm distal to the target lesion are the optimal site for FFR CT measurement, which is in line with previous studies [ 15 , 16 , 18 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings suggest that FFR CT measured at 2 cm distal to the target lesion had the highest performance in identifying lesion-specific ischemia. Overall, our results are consistent with the findings of previous study [ 15 , 16 , 18 , 24 ]. In our study, FFR CT was measured at four different sites along the same artery and our results showed that FFR CT measured at 2 cm distal to the target lesion are the optimal site for FFR CT measurement, which is in line with previous studies [ 15 , 16 , 18 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…Overall, our results are consistent with the findings of previous study [ 15 , 16 , 18 , 24 ]. In our study, FFR CT was measured at four different sites along the same artery and our results showed that FFR CT measured at 2 cm distal to the target lesion are the optimal site for FFR CT measurement, which is in line with previous studies [ 15 , 16 , 18 , 24 ]. It should be noted that the measurement site of the invasive FFR and the definition of the target lesion were not totally consistent between our study and previous studies [ 15 , 16 , 18 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…FFR CT calculations were blindly and independently conducted on CCTA datasets using a software prototype (cFFR, version 3.0.1; Siemens Healthcare). The software is based on the machine learning platform for the noninvasive computation of FFR values using existing CCTA data, and the detailed algorithm has been reported in previous studies 7,15,16 . An observer (Hong Yan Qiao with 5 y of experience in FFR CT analysis), who was blinded to all participants’ baseline clinical data, measured lesion-specific FFR CT values at 2 to 4 cm distal to coronary stenosis in real time.…”
Section: Methodsmentioning
confidence: 99%